Propuesta de plan de mercadeo para un centro de tutorías y recreación después de la escuela, en la provincia de Cartago - Brenes-Winiker, María; Monge-López, Priscilla; Pineda-Cruz, Berta (Instituto Tecnológico de Costa Rica, 2018)
In the present project the main objective was to developed a proposal for a marketing plan based on the Retailing Mix, for an after school tutoring and recreation center in Cartago ́s eastern district, with the title Do & Play After School. The area has a high academic offer with nine private primary schools, with a student population that ranges from 300 to 600 children per center. This is key since it presents a market opportunity. Regarding the potential consumers, it was determined that the target market were parents with school-age children in private schools located in Cartago and would be middle-upper class, middle class, and lower middle class. Currently there is no direct competition in the area. In the analysis for the indirect competition, it was determined that no institution or care center has a specialized focus on school-age children and does not meet the full offer as proposed in Do & Play After School. A market research was conducted through a probe of 69 effective surveys and it was determined that there is a need for the center and that it should be focused on helping children with their homework and provide tutoring. In addition, clubs are considered an added value, as well as the option of lunch and transportation. Once the technical, organizational, legal, environmental, financial and market studies were carried out, the proposal was developed and a communication and sales objectives were established. The necessary strategies for the application of the marketing plan were determined, to detail: As a service strategy, a value proposal was defined in which the trained personnel are highlighted as well as the help with homework, tutoring, clubs, food and transport. The price was determined according to a regular price strategy, fixed to the public based on the market research and the amount paid monthly in the two schools that were used for the research. For the promotion, advertising (open house and a stand at school festivals), direct marketing through email and interactive marketing, on Facebook and Instagram social networks would be applied. In terms of sales, a personalized strategy would be used, the client is known through the activities described in the CMI strategies and through inbound marketing. The characteristics of the employees are detailed according to the needs of the center, with trained personnel in the main areas of study that are taught in private schools. For the presentation of the service, the facilities and characteristics of the center are detailed. The meaning of the name, logo and colors of the center, are related to each other, seeking a unique purpose that is the welfare of the children who attend the center.
Proyecto de Graduación (Maestría en Administración de Empresas) Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas, 2018.
Keywords: Mercadeo; Retailing Mix; Investigación; Estrategia; Servicios